(untitled) (Fiep Bulletin - online, 2012)
This paper is a review of the last three host cities of Olympic Games, Sydney (2000), Athens (2004) and Beijing (2008) addressing the legacies present in their accomplishments. More specifically, we use the scientific literature to look at the structural and sport legacy in the Olympic Games produced for the local population by analyzing the characteristics of these editions. Our overall objective is to identify what were the impacts of investments that occurred in these host cities. While specific goals will identify, in the scientific literature of the Olympic Games, what is meant by legacy, and analyze, from the previous cases of these mega events, which occurred were investments, the interest of cities to host the mega event and the legacy of games, whether considered positive or negative in a general context, with special attention to structural legacies for the people. Regarding the methodology, this study is a descriptive qualitative research, which uses as a source bibliographic data. This was done through books, national and international articles and online portals mentioning investments, bequests and the relationship of both. We emphasize that the literature shows a significant difference in the results, notably on the use and benefit later in the evolution of the country and benefit the local community structures and opportunities of the various cities that have hosted mega-events, from good planning to losses after the Games. Another common view is found on spending more than expected in the construction of these structures, and concern for the environment. Financial issues continue after the completion of events for the maintenance of structures and equipment, restricting their use. However, it is observed an increase in jobs during and after the Games, resulting in a benefit for the local population. For these observations, there is no event considered totally positive, despite the great interest of cities and countries to host them.